Struktura własności ziemskiej w powiecie pilzneńskim w roku 1629 - Anusik, Zbigniew (Przegląd Nauk Historycznych, 2011)
Tax registers of the 16th and 17th century are very useful when doing research on the structure of land ownership in the Polish Republic. One of them is tax register of the county of Pilzno from 1629. It was published in 1977 but it has not been much used by historians so far. Studies conducted by the Author of the research allow to conclude that in terms of a division of land ownership in the county of Pilzno between the king, the church and the nobility (respectively 17,91%; 9,38% and 72,71% of all taxable farmland together with 17,09%; 11,80% and 71,11% of the total amount of tax paid), the results do not differ from calculations made for the whole voivodeship of Sandomierz where at the end of the 16th century Crown lands accounted for 11%, estates of the church amounted to nearly 16% and noble properties accounted for 73% of all real estates in the analyzed voivodeship. The registry here described also confirms common belief that in the first half of the 17th century land was concentrated in hands of large landowners. Eight of the richest landowners representing only 5,48% of all owners (there were 146 of them) gathered in their hands estates which accounted for 38,02% of all taxable farmland and for which the sum of the tax paid amounted to 38,44% of all fiscal charges of the county. Even more impressive are the analogous calculations for the noble property. The wealthiest landowners concentrated in their hands 52,29% taxed farmland and paid to the treasury 54,06% of the tax due to these estates. One should also draw attention to the fact that real estates in the county of Pilzno were owned by so powerful magnates as Ostrogski family and their heirs: Zasławski, Zamoyski and Lubomirski families. Among the wealthiest landowners of the county of Pilzno one can also find representatives of old senatorial families such as Stadnicki, Tarło and Firlej. However, most of them spent their time in properties situated outside the very county. We get even more spectacular results while taking into account real estates burdened with tax higher than 100 zlotys. It appears that 21 landowners representing 14,38% of the whole surveyed population possessed a total of over 50% of all land in the county and paid tax higher than 51% of all revenues to the treasury of the Polish Republic. However, if we take into account estates staying in hands of the nobility only (thus excluding the royal estates and church ones), the results are even more striking. Private landowners owned more than 70% of all taxable farmland and they paid almost 72% of the tax owed. The meaning of these numbers is unambiguous and may serve as a summary of our earlier presentation of the problem.